2013
DOI: 10.4103/2277-9175.107961
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between examination with naked eye, curretage and dermoscopy in determining tumor extension before Mohs micrographic surgery

Abstract: Mohs micrographic surgery (MMS) is a technique for the treatment of cutaneous malignancies. Subtle determination of tumor margin would end to fewer stages of surgery. Our aim was to compare these three ways for determining tumor extension before initiation of MMS, examination with the naked eye, dermoscopy and curettage. Sixty patients who had basal cell carcinoma (BCC) in head and neck area were randomized in three groups (curettage, dermoscopy and examination with the naked eye). Each group encompassed twent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…For example, dermoscopy typically utilizes non-polarized, white light illumination to visualize the skin surface. However, studies have indicated that this technique does not enhance the accuracy of the preoperative tumor margin delineation [ 31 , 32 ]. Recently, RCM and OCT modalities have been combined into a single device for NMSC margin assessment [ 24 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, dermoscopy typically utilizes non-polarized, white light illumination to visualize the skin surface. However, studies have indicated that this technique does not enhance the accuracy of the preoperative tumor margin delineation [ 31 , 32 ]. Recently, RCM and OCT modalities have been combined into a single device for NMSC margin assessment [ 24 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…14 and the existing literature is contradictory (Table 3). 13,[15][16][17][18][19]21 While, some studies demonstrated that dermoscopy significantly decreases the final number of MMS stages, defect size and recurrence rates, 19,20 other reports failed to show a significant reduction of MMS stages using dermoscopy. 13,16,18,21 T A B L E 2 Comparison between examination with naked eye (group 1) and dermoscopy (group 2) in determining tumor extension before slow Mohs surgery Interpretation of the existing literature should be cautious.…”
Section: Discussionmentioning
confidence: 99%